Transcutaneous monitoring of partial pressure of carbon dioxide during endoscopic retrograde cholangiopancreatography using a double‐balloon endoscope with carbon dioxide insufflation under conscious sedation. Issue 3 (13th August 2013) - Miyoshi, Hideaki; Shimatani, Masaaki; Kato, Kota; Sumimoto, Kimi; Kurishima, Akiko; Kusuda, Takeo; Fukata, Norimasa; Ikeura, Tsukasa; Takaoka, Makoto; Okazaki, Kazuichi
<x xml:space="preserve">Abstract</x> Background and Aim A double‐balloon (DB) endoscope can be selectively inserted into the afferent loop to carry out endoscopic retrograde cholangiopancreatography (ERCP) in patients with surgically altered anatomy, allowing various types of endoscopic treatments for pancreaticobiliary diseases to be successfully carried out. In order to make such a lengthy procedure more comfortable and safe, sedatives and carbon dioxide (CO2) insufflation are widely used for gastrointestinal endoscopy. However, these techniques can increase the risk of CO2 retention. Recently, a new sensor for transcutaneous measurement of partial pressure of carbon dioxide (PCO2) has been introduced. The aim of the present study was to evaluate the changes in transcutaneous PCO2 (PtcCO2) during DB‐ERCP with CO2 insufflation under conscious sedation and assess any complications related to sedation and CO2 insufflation. Methods A total of 312 patients underwent DB‐ERCP with CO2 insufflation at our hospital between March 2009 and December 2012. The patients were moderately sedated using midazolamwith or without pentazocine. PtcCO2 was measured by a non‐invasive sensor throughout DB‐ERCP in all patients. Results The mean peak PtcCO2 during the procedure was significantly higher than the mean PtcCO2 value before and after DB‐ERCP. Body mass index, procedure time and dose of pentazocine were significantly higher in the CO2 retention group (peak PtcCO2 ≥ 50 mmHg). CO2 narcosis was observed in one case. Conclusions DB‐ERCP with CO2 insufflation under conscious sedation might have the potential to increase the risk of CO2 retention. Hence, non‐invasive and continuous PtcCO2 measurement is useful for early detection of hypercapnia.